Jüngere Tendenzen der Bevölkerungsentwicklung im Städtesystem Frankreichs - Burdack, Joachim (ERDKUNDE, 1993)
The paper analyses the population development of French urban agglomerations of more than 50000 inhabitants over the last three decades (1962-90). Trends of net migration, natural increase and total population change are examined with respect to different functional and structural city types. The results show changes of long established growth patterns: an overall decrease of urban growth rates in the seventies and the resurgence of the growth of the largest metropolitan areas in the eighties. Although more empirical evidence is needed to confirm the new trends, the findings can be linked to hypotheses that interpret the new growth patterns as resulting from the overlap of two diffusion processes: the fading out of industrial decentralization that leads to decreased growth in smaller and medium -sized urban areas and the take-off of a new innovation process based on telecommunication and internationalization of production that favours the growth of the largest cities.